Mostra de Saberes - Bressanin , Maxlane Aparecida Teixeira; Cardoso , Aparecida do Carmo; Silva , Sonia Andrade da; Ponce, Ana Claudia da Silva; Carraro , Marcia Regina Simpioni (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2023)
>>> ver pdf